2012
DOI: 10.5589/q12-004
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory tracking control of flexible-joint space manipulators

Abstract: The research of the automatic control for the key technology of space flexible manipulators is a leading task in the current scientific research. According to the groundbreaking research results of the key technology of dynamics modeling and automatic control for robots obtained by the researchers in recent years, this paper carries out a comprehensive analytic demonstration and summarization on the key technology of automatic control for flexible manipulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lassard et al [9] applied the singular perturbation method along with feed-forward control to a flexible robotic system the results show that both methods settle the system at the same time though for the feed-forward method, the nonlinear terms are neglected for the application of this method. Ulrich and Sasiadek [10] worked on the flexible joint to control the system and applied the singular perturbation method along with the model reference adaptive controller, they found that the adaptive control strategy has greater tracking accuracy than the singular perturbation method. Zaare et al [11] analyzed the stability of a system in both structured and unstructured uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Lassard et al [9] applied the singular perturbation method along with feed-forward control to a flexible robotic system the results show that both methods settle the system at the same time though for the feed-forward method, the nonlinear terms are neglected for the application of this method. Ulrich and Sasiadek [10] worked on the flexible joint to control the system and applied the singular perturbation method along with the model reference adaptive controller, they found that the adaptive control strategy has greater tracking accuracy than the singular perturbation method. Zaare et al [11] analyzed the stability of a system in both structured and unstructured uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of needing an additional link-side torque sensor was later addressed by ( Ulrich and Sasiadek, 2012a ), where an extended Kalman filter was used to estimate the link-side state for a 2 degree-of-freedom (DOF) robot in simulation. Adaptive control has been utilized to reduce trajectory tracking error for a 2 DOF robot with a floating base ( Ulrich et al, 2012 ; Ulrich and Sasiadek, 2012a ; Ulrich and Sasiadek, 2012b ). However, this strategy leads to large motor torque values when there are sharp changes in the end-effector path.…”
Section: Introductionmentioning
confidence: 99%
“…7 The high acceleration and jerk can lower the precision of trajectory tracking and cause large residual vibration. 8 Moreover, when undertaking the teleoperation tasks, different operators have different proficiencies and cannot sense the acceleration and jerk calculated by the inverse kinematics quantitatively. The time delay of space robot teleoperation system is so large that the effect of current manipulation on the space robot is difficult to predict.…”
Section: Introductionmentioning
confidence: 99%